Celebrity Endorsements and Millennial Purchase Decisions on Instagram - Lidya Chitra Laoh (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the influence of celebrity endorsements on purchasing decisions for millennials on Instagram. To answer the research questions, data were collected on 471 students as research objects using a questionnaire. A simple regression method was used to analyze the collected data. The results of this study's data analysis found that celebrity endorsements were influential in determining millennial generation purchasing decisions